1992
DOI: 10.1128/mcb.12.9.4209
|View full text |Cite
|
Sign up to set email alerts
|

Functional antagonism between YY1 and the serum response factor.

Abstract: The rapid, transient induction of the c-fos proto-oncogene by serum growth factors is mediated by the serum response element (SRE). The SRE shares homology with the muscle regulatory element (MRE) of the skeletal ce-actin promoter. It is not known how these elements respond to proliferative and cell-type-specific signals, but the response appears to involve the binding of the serum response factor (SRF) and other proteins. Here, we report that YY1, a multifunctional transcription factor, binds to SRE and MRE s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
155
3

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(164 citation statements)
references
References 25 publications
6
155
3
Order By: Relevance
“…This could be accounted for by di erences in CREBP phosphorylation or by di erent co-activators/repressors associated with CREBP in these cells. YY1 sites in the c-fos promoter adjacent to SRE and CRE sites have demonstrated positive and negative regulatory e ects through interactions of YY1 with proteins bound to these response elements (Natesan and Gilman, 1993Gilman, ,1995Gualberto et al, 1992). A YY1 site distinct from the ones adjacent to the SRE and CRE was actively bound in tumorigenic 1170I cells, and the role of this YY1 site has not been examined previously.…”
Section: Discussionmentioning
confidence: 99%
“…This could be accounted for by di erences in CREBP phosphorylation or by di erent co-activators/repressors associated with CREBP in these cells. YY1 sites in the c-fos promoter adjacent to SRE and CRE sites have demonstrated positive and negative regulatory e ects through interactions of YY1 with proteins bound to these response elements (Natesan and Gilman, 1993Gilman, ,1995Gualberto et al, 1992). A YY1 site distinct from the ones adjacent to the SRE and CRE was actively bound in tumorigenic 1170I cells, and the role of this YY1 site has not been examined previously.…”
Section: Discussionmentioning
confidence: 99%
“…YY-1 binding sites were found in many genes Hariharan et al, 1991;Park and Atchison, 1991;Flanagan et al, 1992) and in most cases, YY-1 exerts its activating or repressing functions through physical and/or functional interaction with other nuclear proteins (Seto et al, , 1993May et al, 1994;Nateson et al, 1993;Lee et al, 1993;Gualberto et al, 1992;Inouye and Seto, 1994;Ushva and Shenk, 1994;Raich et al, 1995). Thus, in the present study, we examined how YY-1 can regulate the LCR-like activity of the mouse glycophorin gene through its interaction with other proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Within this region there exist 6 di erent nuclear factor binding sites: GATA-1, NF-E2, Spi-1/PU.1, GGTGG , YY-1 and E-box. YY-1, a GLI-Kruppel-related zinc ®nger protein, is a ubiquitously present versatile nuclear transcription factor Hariharan et al, 1991;Park and Atchison, 1991), and regulates expression of many genes by binding to the regulatory elements of these genes (Seto et al, , 1993May et al, 1994;Nateson et al, 1993;Lee et al, 1993;Gualberto et al, 1992;Inouye and Seto, 1994;Ushva and Shenk, 1994;Raich et al, 1995). We examined the functional involvement of YY-1 and the E-box binding protein (EBP) on the LCR-like activity of the mouse glycophorin gene by stably transfecting the mutants in the YY-1 binding site and the neighboring E-box binding site into MEL cells; we demonstrated that YY-1 acts as a regulatory protein in combination with EBP and may regulate LCR-like activity of the mouse glycophorin gene (Nemoto et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Other factors binding the SRE that have been identi®ed include NFIL6/c/EBPb, YY1, SRE-ZBP and TFII-I-Phox1 (Attar and Gilman, 1992;Grueneberg et al, 1997;Gualberto et al, 1992;Kim et al, 1998;Metz and Zi , 1991). None of these are likely to account for band 3 or the faint band migrating below band 4 in Figure 3a, since they would not be expected to be competed by the FAP1 oligonucleotide which does not span their binding sites (Attar and Gilman, 1992;Grueneberg et al, 1997;Gualberto et al, 1992;Kim et al, 1998;Metz and Zi , 1991).…”
Section: Atf1 and Creb Bind The Fap1 Sitementioning
confidence: 99%
“…None of these are likely to account for band 3 or the faint band migrating below band 4 in Figure 3a, since they would not be expected to be competed by the FAP1 oligonucleotide which does not span their binding sites (Attar and Gilman, 1992;Grueneberg et al, 1997;Gualberto et al, 1992;Kim et al, 1998;Metz and Zi , 1991). E12 was also found to bind the SRE and may bind the FAP1 sequence since it contains its core CANNTG binding site (Metz and Zi , 1991).…”
Section: Atf1 and Creb Bind The Fap1 Sitementioning
confidence: 99%